Pengaruh Bauran Pemasaran terhadap Keputusan Pengajuan Kredit Nasabah Bank NTT - Adrianus Ketmoen; Hwihanus; Maria Imakulata Pongge (Universitas Pendidikan Ganesha, 2026)
This study analyzes the effect of the marketing mix on customers’ credit application decisions at Bank NTT. The background of this research lies in the fluctuation of credit distribution target achievement during 2018–2022, indicating that the growth in debtors was not consistently followed by the attainment of lending targets. The study applies a quantitative cross-sectional design with 175 respondents selected purposively from Bank NTT customers who had applied for credit. Data were collected through questionnaires and analyzed using descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that customers generally perceive Bank NTT’s marketing mix and credit application decisions as good to very good. Partially, product, price, promotion, people, and physical evidence have a positive and significant effect on credit application decisions. In contrast, place and process have a negative and insignificant effect. Simultaneously, the seven dimensions of the marketing mix significantly affect credit application decisions. The model explains 53.1 percent of the variation in credit application decisions. These findings imply that Bank NTT needs to strengthen product competitiveness, pricing transparency, promotional effectiveness, service quality, and physical evidence while improving process efficiency and branch accessibility.